2022
DOI: 10.3389/fmars.2022.945330
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Evolution and Nitrogen Behaviors in Coastal Groundwater Suffered From Seawater Intrusion and Anthropogenic Inputs

Abstract: Coastal aquifers play key roles in providing freshwater resources to maintain the social and economic development in coastal areas. However, climate change and human activities have dramatically affected the quantities and qualities of groundwater in coastal aquifers. In this study, stoichiometric analysis of hydrogeochemistry, multivariate analysis, and isotopic trancing techniques were used to reveal the local hydrochemistry characteristics, the natural and anthropogenic origins, and the major hydrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The source of water can be identified using stable isotopes of hydrogen (dD) and oxygen (d 18 O). (Han et al, 2020;Carretero et al, 2022;Dun et al, 2022). In this study, we investigated the hydrochemical characteristics, stable isotopes of hydrogen and oxygen, and sedimentary environmental changes in the study area to understand the origin and mechanisms of groundwater salinization at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…The source of water can be identified using stable isotopes of hydrogen (dD) and oxygen (d 18 O). (Han et al, 2020;Carretero et al, 2022;Dun et al, 2022). In this study, we investigated the hydrochemical characteristics, stable isotopes of hydrogen and oxygen, and sedimentary environmental changes in the study area to understand the origin and mechanisms of groundwater salinization at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…Except for LB2, all the lake sources fell in the middle of the Gibbs diagram, reflecting the influence of evaporation, rock interaction, and rainfall in driving the cation composition of the lake water sources. As Dun et al (2022) observed in the Pearl River Estuary in China, rock-water interactions often characterize flow delayed in porous aquifers. As such, the samples within the Babati catchment with higher ion concentrations must have had the opportunity for rock-water dissolution.…”
Section: Gibbs Diagrammentioning
confidence: 77%